Feeling It Out: The Use of Haptic Visualization for Exploratory Geographic Analysis - Griffin, Amy L. (Cartographic Perspectives, 2001)
Visualization is often defined as the act or process of making something visible. MacEachren and Ganter (1990) have argued for an expanded definition of cartographic visualization that emphasizes the role of the map-reader’s cognitive processes and schemata when creating visual representations. Cartographic visualization in this sense requires both the designer and the user to structure information and identify salient patterns. Processes of pattern identification and structuring are what help to provide insight in exploratory analysis. Pattern identification and information structuring need not, however, be limited to the visual realm. The use of haptic (both tactual and kinesthetic) information for representing geographic phenomena has been given limited attention as a method for exploring data, due to the difficulty of implementing such methods. However, advances in virtual reality technologies may soon make it possible to implement these variables in a system that creates exploratory geographic virtual environments. This paper explores those haptic variables that might be used to create such representations, and develops a haptic variable syntax for the representation of geographic information based on a logical analysis of the physiological properties of haptic sensation.